2003
DOI: 10.1523/jneurosci.23-22-08159.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations indeadly seven/notch1aReveal Developmental Plasticity in the Escape Response Circuit

Abstract: The relatively simple neural circuit driving the escape response in zebrafish offers an excellent opportunity to study properties of neural circuit formation. The hindbrain Mauthner cell is an essential component of this circuit. Mutations in the zebrafish deadly seven/notch1a (des) gene result in supernumerary Mauthner cells. We addressed whether and how these extra cells are incorporated into the escape-response circuit. Calcium imaging revealed that all Mauthner cells in desb420 mutants were active during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…This reflex involves the integration of sensory input from Rohon-Beard neurons in the spinal cord and motor output from the hindbrain and a large number of interneurons. [37][38][39][40][41][42][43][44][45] Arnt2 À=À larvae were predominantly unreactive to vibrational or tactile stimuli, suggesting that Arnt2 is associated with a part of the neural network that coordinates this response. Neuromasts are present in the arnt2 À=À mutants, which together with the overall intact structure of the inner ear suggests that auditory sensation, as well as vibrational sensation (lateral line), is not affected by loss of Arnt2.…”
Section: Role Of Arnt2 In Development Of the Startle And Touch Responsesmentioning
confidence: 99%
“…This reflex involves the integration of sensory input from Rohon-Beard neurons in the spinal cord and motor output from the hindbrain and a large number of interneurons. [37][38][39][40][41][42][43][44][45] Arnt2 À=À larvae were predominantly unreactive to vibrational or tactile stimuli, suggesting that Arnt2 is associated with a part of the neural network that coordinates this response. Neuromasts are present in the arnt2 À=À mutants, which together with the overall intact structure of the inner ear suggests that auditory sensation, as well as vibrational sensation (lateral line), is not affected by loss of Arnt2.…”
Section: Role Of Arnt2 In Development Of the Startle And Touch Responsesmentioning
confidence: 99%
“…Liu et al (2003) found that in the des b420 , all M-cells appear to respond to startle stimuli, and they respond simultaneously, suggesting that they are receiving similar sensory input. In addition, although multiple M-cells were active in response to a startle stimulus, the additional activity did not enhance behavioral performance (Liu et al, 2003). We found similar results for fish with ectopic M-cells generated by hoxb1b misexpression; although both r2 and r4 M-cells were active in response to startle stimuli, behavioral performance remained the same.…”
Section: The Role Of Multiple Mauthner Cells In Startle Behaviormentioning
confidence: 95%
“…The live mounted fish was covered with HBSS to prevent drying. The dish was placed on the stage of an inverted confocal microscope (model 510; Zeiss, Thornwood, NY), and a fine glass tapper actuated with an electric current was positioned against the side of the body on the ipsilateral side to the M-cells being investigated, as described previously (Liu et al, 2003). A time series of images was recorded beginning before application of the startle stimulus and lasting until the fluorescence levels in the cell returned to baseline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Fetcho et al (1997) have been able to engineer certain classes of cells to express Ca 2C -sensitive dyes so that the development of complex connections between nerves can be determined (Higashijima et al 2003;Liu et al 2003). Finally, as the genetic approaches evolve, one would anticipate the ability to modify specific molecular aspects of muscle function (i.e.…”
Section: Cmentioning
confidence: 99%